Impact of EGFR mutations and KRAS amino acid substitution on the response to radiotherapy for brain metastasis of non-small-cell lung cancer. (January 2016) - Renaud, Stéphane; Schaeffer, Mickaël; Voegeli, Anne-Claire; Legrain, Michèle; Guérin, Eric; Meyer, Nicolas; Mennecier, Bertrand; Quoix, Elisabeth; Falcoz, Pierre-Emmanuel; Guénot, Dominique; Massard, Gilbert; Noël, Georges; et al.
Background: Our study aimed to evaluate response rate (RR) to brain metastasis radiotherapy (RT), depending on the genomic status of non-small-cell lung cancer.Material & methods: We retrospectively reviewed 1971 non-small-cell lung cancer files of patients with EGFR and KRAS testing and focused on 157 patients who had undergone RT for brain metastasis.Results: A total of 16 patients (10.2%) harbored EGFR mutations (m EGFR ) and 45 patients (28.7%) KRAS (m KRAS ). In univariate analysis, RR was significantly higher for m EGFR compared with wild-type EGFR/KRAS (odds ratio [OR]: 4.96; p = 0.05) or m KRAS (OR: 1.81; p = 0.03). In multivariate analysis, KRAS G12V or G12C status was associated with both poor RR (OR: 0.1; p < 0.0001) and overall survival (OR: 3.41; p < 0.0001).Conclusion: m EGFR are associated with higher RR to brain RT than wild-type EGFR/RAS or m KRAS .